PkM Penguatan Kapasitas Mengukur dan Verifikasi Arah Kiblat bagi Pengurus Masjid - Sakirman Sakirman; A Jamil; Moelki Fahmi Ardliansyah (Universitas Nurul Jadid, 2023)
The needs of Muslims in ruhiyah are to be able to perform prayers in the mosque with khusyu', which is characterized by the fulfillment of the conditions for the validity of prayer, namely facing the face and limbs towards the qibla both during ruku and prostration. The mosque as a place of worship for Muslims must be accurately measured facing the Kaaba. The role of mosque administrators as assisted subjects has a considerable contribution to community change. Through mosque administrators, public trust can be integrated, when there is a debate about Qibla direction. How to provide an understanding to mosque administrators of the importance of Qibla direction and verification of mosques sampled in this service research is a problem that will be unraveled. this study program-based service-research is based on qualitative research. The approach used is participatory action research or participation research. This approach aims to see, hear, and understand social symptoms that occur in society. The results obtained through this service-research are based on the verification results of the al-Hidayah mosque, al-Jihad mosque, Baiturrohman II mosque, Nur Hidayah mosque, and Nurul Iman mosque, it can be concluded that the accuracy level of the five mosques is very low.